A Phase 2 Study of Allogeneic Mesenchymal Stromal Cells for Luminal Crohn's Disease Refractory to Biologic Therapy - Forbes, Geoffrey M.; Sturm, Marian J.; Leong, Rupert W.; Sparrow, Miles P.; Segarajasingam, Dev; Cummins, Adrian G.; Phillips, Michael; Herrmann, Richard P. (Clinical gastroenterology and hepatology, 2014)
Transplantation of peripheral blood stem cells has been successful therapy for small numbers of patients with Crohn’s disease (CD), but requires prior myeloconditioning. Mesenchymal stromal cells (MSCs) escape immune recognition, so myeloconditioning is not required before their administration. We investigated the efficacy of allogeneic MSCs in patients with luminal CD. Our phase 2, open-label, multicenter study included 16 patients (21–55 y old; 6 men) with infliximab- or adalimumab-refractory, endoscopically confirmed, active luminal CD (CD activity index [CDAI], >250). Subjects were given intravenous infusions of allogeneic MSCs (2 × 106 cells/kg body weight) weekly for 4 weeks. The primary end point was clinical response (decrease in CDAI >100 points) 42 days after the first MSC administration; secondary end points were clinical remission (CDAI, <150), endoscopic improvement (a CD endoscopic index of severity [CDEIS] value, <3 or a decrease by >5), quality of life, level of C-reactive protein, and safety. Among the 15 patients who completed the study, the mean CDAI score was reduced from 370 (median, 327; range, 256–603) to 203 (median, 129) at day 42 (P < .0001). The mean CDAI scores decreased after each MSC infusion (370 before administration, 269 on day 7, 240 on day 14, 209 on day 21, 182 on day 28, and 203 on day 42). Twelve patients had a clinical response (80%; 95% confidence interval, 72%–88%; mean reduction in CDAI, 211; range 102–367), 8 had clinical remission (53%; range, 43%–64%; mean CDAI at day 42, 94; range, 44–130). Seven patients had endoscopic improvement (47%), for whom the mean CDEIS scores decreased from 21.5 (range, 3.3–33) to 11.0 (range, 0.3–18.5). One patient had a serious adverse event (2 dysplasia-associated lesions), but this probably was not caused by MSCs. In a phase 2 study, administration of allogeneic MSCs reduced CDAI and CDEIS scores in patients with luminal CD refractory to biologic therapy. ClinicalTrials.gov number, NCT01090817.